A coating containing liquid metal and its preparation method and application

By using the use of liquid -containing metal composite powder on the base surface to solve the problem of excessive thickness of liquid metal coating and scratch resistance on the surface, the coating preparation of high mechanical stability and scratch resistance is available. Base of material and form.

CN115613027BActive Publication Date: 2025-01-28SICHUAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211277363.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-19
Publication Date
2025-01-28
Estimated Expiration
2042-10-19

AI Technical Summary

Technical Problem

The existing liquid metal coating is too thick, the surface is not resistant to scratches, and the preparation method is complex, and the applicable scenarios are limited.

Method used

The composite powder with liquid metal metal forms a uniform coating on the base surface by rubbing the coating method. The adhesion of the liquid metal and its oxidation layer can be used to achieve the uniform spread of coating and the wipe of the solid filler. Sex and scratch resistance.

Benefits of technology

The nano -to micron can be adjusted by the thickness of the coating, which significantly improves the mechanical stability and scratch resistance of the coating, simplifies the preparation process, expands the applicable scenarios, and the coating conductivity thermal conductivity is close to metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115613027B_ABST
    Figure CN115613027B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of functional material preparation, and specifically to a preparation method and application of a coating containing liquid metal. The present invention provides a coating containing liquid metal, wherein the coating is a uniform coating containing liquid metal formed by coating a composite powder containing liquid metal on the surface of a substrate; wherein the composite powder containing liquid metal is a mixture formed by liquid metal and solid filler, and the weight ratio of liquid metal to solid filler is: 30 to 90 parts by weight of liquid metal, 10 to 70 parts by weight of solid filler. In view of the technical problems such as the current existing liquid metal coating being too thick and the surface being not scratch-resistant, the present invention provides a coating containing liquid metal, the thickness of the obtained coating can be adjusted from nanometer to micrometer scale, and the coating has excellent mechanical stability and scratch resistance on the substrate surface; and the method for preparing the coating of the present invention is simple to operate, and can be processed on substrates of different materials and shapes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional material preparation, and in particular to a preparation method of a coating containing liquid metal and application thereof. Background Art

[0002] Liquid metal is a special metal with metallic conductivity and liquid ductility, which can be used in drug delivery, microfluidics, sensing, catalysis, flexible electronic devices, batteries, electromagnetic shielding and optics. However, the high surface tension of liquid metal (>600N / m) hinders its wetting on the surface of most materials and uniform micro-nanoscale coating processing; and its liquid properties make the device prone to leakage loss during the packaging process.

[0003] At present, the reported liquid metal processing strategies mainly include emulsion dispersion, spray printing, mask printing, 3D printing, flexographic printing, direct writing, coaxial printing, freeze casting and laser-assisted printing. In addition, liquid metal composite materials (modified liquid metal formed by the composite of inorganic materials and liquid metal) have been reported to be used for liquid metal molding. The above processing methods are mainly aimed at the preparation of flexible circuits urgently needed by flexible electronic materials. Although the relevant processing technology has achieved great success, with the promotion of the application scope of liquid metal, the processing of liquid metal still needs to develop new technologies to meet the needs of different scenarios. For example, there is still a lack of simple, effective and universal surface submicron and nanometer thickness coating technology for liquid metal; at the same time, in addition to the need to further reduce the thickness of the existing liquid metal coating, the scratch resistance of the coating is also urgently needed to be improved. There have been reports on the preparation of micro-nano liquid metal films through scraping, spin coating, adhesion transfer, and dipping techniques, as well as improving the stability of liquid metal through Bi alloying of liquid metal and dispersed distribution of Ag. However, these processes are complicated to operate, have limited applicable scenarios (one-dimensional and three-dimensional materials are difficult to prepare), and lack scalability and mechanical stability of the coating. Summary of the invention

[0004] The present invention aims to solve the technical problems of existing liquid metal coatings being too thick and not scratch-resistant, and provides a coating containing liquid metal. The thickness of the resulting coating can be adjusted from nanometers to micrometers, and the coating has excellent mechanical stability and scratch resistance on the substrate surface. The method for preparing the coating of the present invention is simple to operate, and can be processed on substrates of different materials and shapes. The technical problems of complex operation and limited applicable scenarios in existing preparation methods are solved, and new ideas and strategies are provided for new micro-nano processing of liquid metals.

[0005] The technical solution of the present invention:

[0006] The first technical problem to be solved by the present invention is to provide a coating containing liquid metal, wherein the coating is a uniform coating containing liquid metal formed by coating a composite powder containing liquid metal on the surface of a substrate; wherein the composite powder containing liquid metal is a mixture of liquid metal and solid filler, and the weight ratio of the liquid metal to the solid filler is: 30 to 90 parts by weight of liquid metal and 10 to 70 parts by weight of solid filler.

[0007] Preferably, the weight ratio of the liquid metal to the solid filler is: 30 to 70 parts by weight of the liquid metal and 30 to 70 parts by weight of the solid filler.

[0008] Furthermore, the thickness of the coating containing liquid metal is 1 nm to 5 μm.

[0009] Furthermore, the coating containing liquid metal has no obvious scratches after being rubbed with 1000-grit sandpaper for 50 cm under a pressure of 0.5 kPa.

[0010] Furthermore, the liquid metal-containing composite powder is prepared by the following method: the liquid metal and the solid filler are ground by mortar, ball mill, mechanical stirring, or solvent-based mechanical or ultrasonic emulsification mixing.

[0011] Furthermore, the particle size of the composite powder containing liquid metal is 1 to 100 μm.

[0012] Furthermore, the coating containing liquid metal is prepared by the following method: a composite powder containing liquid metal is used to form a uniform coating containing liquid metal on the surface of the substrate by a rubbing process, and the rubbing process is as follows: the composite powder containing liquid metal is contacted with the surface of the substrate, and the liquid metal in the powder is first spread evenly on the surface of the substrate by repeated rubbing at a pressure P1 and a friction rate V1; then, the surface of the substrate is made to show a uniform bright color and no excess powder by repeated rubbing at a pressure P2 and a friction rate V2; that is, a uniform coating containing liquid metal is formed. In the initial stage of rubbing, a certain pressure and friction are applied to make a large amount of liquid metal and a small amount of solid filler in the composite powder containing liquid metal spread on the surface of the substrate first; in the later stage of rubbing, the solid filler is rubbed into the liquid metal coating under a certain pressure and friction and forms a uniform thin layer of solid filler on its upper surface, so that the surface of the coating containing liquid metal obtained in the end is uniform and the mechanical stability is significantly improved.

[0013] Furthermore, P1=1N~300N (10Kpa-3000Kpa), P2=0.1N~35N (1Kpa-350Kpa), V1=1~10cm / s, V2=1~30cm / s.

[0014] Preferably, P1=3N~80N (300Kpa-800Kpa), P2=0.5N~30N (5Kpa-300Kpa).

[0015] Furthermore, the substrate is: one-dimensional fiber, two-dimensional film or sheet, three-dimensional porous material, or: regular or irregular block. It can be seen that the present invention can realize the conductive coating processing on the surface of any material such as one-dimensional fiber, two-dimensional film and sheet, three-dimensional porous and regular or irregular block by rubbing method, thereby broadening the application scope of liquid metal coating from the processing method, so as to prepare conductive composite materials with different functional uses.

[0016] Furthermore, the one-dimensional fiber includes: polymer fiber, glass fiber or basalt fiber; the two-dimensional film includes: polymer film, battery separator or metal foil; the three-dimensional structural material includes: foam, ceramic products or pipe inner wall, etc.

[0017] Furthermore, in the composite powder containing liquid metal, the liquid metal includes common composite liquid metals of various compositions at room temperature and low-temperature metal melts (melting point below 400° C.).

[0018] Furthermore, the liquid metal includes at least one of gallium metal, gallium-indium alloy, gallium-indium-tin alloy, mercury metal, francium metal, cesium metal, lithium metal, sodium metal, potassium metal, rubidium metal, cesium metal, zinc metal, cadmium metal or bismuth metal.

[0019] Furthermore, the solid filler includes: carbon-based solid filler, metal oxide, solid metal filler, solid ceramic filler or electrode active particle filler.

[0020] Furthermore, the carbon-based solid filler includes at least one of natural graphite, artificial graphite, flake graphite, block graphite, cryptocrystalline graphite, graphene powder, carbon nanotube powder or carbon micro-nanosphere powder;

[0021] The metal oxide includes at least one of indium oxide, gallium oxide, tin oxide, ferroferric oxide, ferrous oxide, manganese oxide, chromium oxide, aluminum oxide, titanium dioxide, silicon dioxide, nickel oxide, calcium oxide, sodium oxide, magnesium oxide, barium oxide, iron oxide, copper oxide or molybdenum oxide;

[0022] The solid metal filler comprises at least one of silver powder, gold powder, copper powder, aluminum powder, zinc powder, magnesium powder, tin powder, iron powder, tungsten powder, molybdenum powder, nickel powder, cobalt powder, lead powder, titanium powder or tantalum powder;

[0023] The solid ceramic filler includes: boron carbide, chromium carbide, molybdenum carbide, silicon carbide, titanium carbide, zirconium carbide, vanadium carbide, aluminum nitride, boron nitride, silicon nitride, titanium nitride, chromium diboride, titanium diboride, zirconium diboride, ZIF materials, MoS2, MOF (such as IRMOF, PCN, MIL, UIO series materials), MXene (Ti2CT x ,TiNbCT x ,Ti3CN x T x ,Ta4C3T x ,Nb2CT x ,V2CT x ,Nb4C3T x ,Mo2CT x ), GO (single-layer, double-layer, multi-layer graphene), rGO, Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 、Li7La3Zr2O 12 、LiTi2(PO4)3、LiGe2(PO4) 3、 Li6PS5Cl, Li6PS5 Br, Li6PS5 I, Li 10 GeP2S 12 and Li7P3S 11 At least one of;

[0024] The electrode active particle fillers include: LiCoO2, NCM (such as NCM532, NCM811), LiMn2O4, LiFeO4 and NCA (LiNi 0.8 Co 0.15 Al 0.05 O2) at least one.

[0025] The second technical problem to be solved by the present invention is to provide a preparation method for the above-mentioned liquid metal-containing coating, the preparation method being: forming a uniform liquid metal-containing coating on the surface of a substrate by a rubbing processing method using a composite powder containing liquid metal, the rubbing processing method being: bringing the composite powder containing liquid metal into contact with the surface of the substrate, first by repeatedly rubbing at a pressure P1 and a friction rate V1 so that the liquid metal in the powder can be evenly spread on the surface of the substrate; then by repeatedly rubbing at a pressure P2 and a friction rate V2 so that the surface of the substrate appears to be a uniform bright color and there is no excess powder, that is, a uniform liquid metal-containing coating is formed.

[0026] Furthermore, P1=1N~300N (10Kpa-3000Kpa), P2=0.1N~35N (1Kpa-350Kpa), V1=1~10cm / s, V2=1~30cm / s.

[0027] Preferably, P1=3N~80N (300Kpa-800Kpa), P2=0.5N~30N (5Kpa-300Kpa).

[0028] Furthermore, in the above method, flexible and easily deformable tool materials can be used for wiping, and the tool materials include: porous plastic foam, fiber felt, rubber sheet, cellulose-based film, paper and other flexible and easily deformable materials. The above flexible wiping tool materials are obviously different from other processing tools (scrapers, brushes, etc.). Take foam as an example: soft foam with a porous structure can realize the loading of liquid metal composite powder, can effectively transmit pressure and achieve a high friction coefficient with the substrate. During the wiping process, the foam confines the composite powder to a certain area to rub against the substrate material, and the liquid metal and powder are released step by step, realizing the uniform preparation of the liquid metal coating.

[0029] Furthermore, the method for preparing the coating containing liquid metal comprises the following steps:

[0030] 1). Prepare a mixture of liquid metal and solid filler to form a composite powder that is easy to flow;

[0031] 2) Dispersing the composite powder onto the surface of the substrate to be coated, or onto the surface of a flexible wiping tool material;

[0032] 3). Apply pressure and friction to the composite powder and the substrate to be coated by a flexible wiping tool material, first spread the composite powder evenly on the substrate surface by repeated wiping at a pressure of P1 and a friction rate of V1; then, make the substrate surface coating uniform and free of excess powder by repeated wiping at a pressure of P2 and a friction rate of V2; then remove the excess powder to form a uniform, stable and strong coating containing liquid metal; the liquid metal automatically forms a composite coating on any surface under the micro-adhesion force of its surface oxide, solid filler and substrate.

[0033] The present invention can realize arbitrary coating and molding on the surfaces of one-dimensional fibers (polymer fibers, glass fibers, basalt fibers, etc.), two-dimensional films (polymer films, battery separators, metal foils, etc.), three-dimensional foams, ceramic products, inner walls of pipes, etc. The obtained composite coating is not only scratch-resistant, but also has electrical and thermal conductivity properties close to those of metals.

[0034] The third technical problem to be solved by the present invention is to provide the application of the above-mentioned liquid metal-containing coating in 1D, 2D, 3D conductive materials or anode-free lithium metal batteries.

[0035] The fourth technical problem to be solved by the present invention is to provide a method for preparing a coating using a flowable metal or its composite powder, the method comprising: forming a coating on the surface of a substrate by a rubbing method using a flowable metal or its composite powder, the rubbing method comprising: firstly rubbing repeatedly at a pressure P1 and a friction rate V1 so that the flowable metal or the flowable metal in the composite powder can be evenly spread on the surface of the substrate; then rubbing repeatedly at a pressure P2 and a friction rate V2 so that the surface of the substrate exhibits a uniform bright color and is free of excess powder; that is, a uniform coating containing flowable metal is formed.

[0036] Furthermore, P1=1N~300N (10Kpa-3000Kpa), P2=0.1N~35N (1Kpa-350Kpa), V1=1~10cm / s, V2=1~30cm / s.

[0037] Preferably, P1=3N~80N (300Kpa-800Kpa), P2=0.5N~30N (5Kpa-300Kpa).

[0038] Furthermore, the flowable metal is: liquid metal, modified liquid metal (modified substance containing liquid metal, such as the above-mentioned composite powder containing liquid metal), molten lithium metal, sodium metal, potassium metal, zinc metal or bismuth metal, etc. When the liquid metal adopts the rubbing coating method of the present invention, the liquid metal coating prepared on the copper foil by the rubbing coating processing method can be applied to anode-free lithium metal batteries, and its cycle stability performance is significantly improved compared with untreated copper foil.

[0039] Beneficial effects of the present invention:

[0040] The present invention provides a method for preparing a coating containing liquid metal, wherein the method automatically forms the liquid metal coating on any substrate surface by contacting the liquid metal composite powder with the substrate surface by rubbing, under the micro-adhesion force of the liquid metal and its surface oxide layer on the substrate surface, thereby preparing a stable, scratch-resistant coating containing liquid metal with metal-level conductive properties. The composite conductive coating of the present invention can be stably adhered to the substrate, and the coating has no obvious scratches after rubbing and moving 50cm with 1000-mesh sandpaper under a pressure of 0.5kPa. At the same time, the present invention realizes arbitrary coating and forming on the surfaces of one-dimensional fibers (polymer fibers, glass fibers, basalt fibers, etc.), two-dimensional films (polymer films, battery separators, metal foils, etc.), three-dimensional foams, ceramic products, inner walls of pipelines, etc. The obtained composite coating is not only scratch-resistant, but also has electrical and thermal conductivity close to that of metals. In addition, the method has the characteristics of simple operation, wide application scenarios, and good scale-up capability. At the same time, the mechanical stability and scratch resistance of the coating on the substrate surface are greatly enhanced, providing new ideas and strategies for new micro-nano processing of liquid metals. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a flow chart for preparing a liquid metal coating and the corresponding liquid metal composite powder according to Example 5 of the present invention.

[0042] Figure 2 is an optical image of a liquid metal coating obtained on the surface of a glass substrate in Example 1 of the present invention; Figure 2 It can be seen that the upper layer of the surface of the liquid metal coating is mainly a graphite layer, and the lower layer is mainly a liquid metal layer.

[0043] Figure 3 Embodiments 2, 5 and 6 of the present invention are coated on glass ( Figure 3 In Example 2), copper foil ( Figure 3 Next, Example 5), ceramic ( Figure 3 , Example 6) formed by the optical and conductive properties of the surface containing the liquid metal coating; Figure 3 It can be seen that the method of the present invention can form a uniform coating on the surface of 3D ceramics, glass, and copper foil, and the coated material has excellent conductive properties.

[0044] Figure 4 Optical photographs of the uniform state of the coating surface obtained by Example 15 (preparation of liquid metal coating by rubbing coating method) of the present invention, Comparative Example 1 (preparation of liquid metal coating by adhesion transfer method), Comparative Example 2 (preparation of liquid metal coating by scraping coating method); Example 2 (processing of liquid metal composite powder by rubbing coating method), Comparative Example 3 (processing of liquid metal composite powder by adhesion transfer method), Comparative Example 4 (processing of liquid metal composite powder by scraping coating method); Figure 4It can be seen that: compared with the adhesive transfer method and the blade coating method, the rubbing coating method can achieve uniform preparation of the coating containing the flowable metal or its composite powder on the substrate surface (Example 15, Example 2).

[0045] Figure 5 The figure is a comparison chart of the uniformity, wear resistance and peeling characteristics of the liquid metal coating prepared by the inventive example 2 (processing liquid metal composite powder by rubbing coating method) and the comparative example 1 (preparing liquid metal coating by adhesive transfer method) and the comparative example 2 (preparing liquid metal coating by scraping coating method); Figure 5 It can be seen that the uniform processing of liquid metal composite powder is achieved through the rubbing method. Compared with the liquid metal coating, its mechanical stability and anti-peeling performance are greatly enhanced. Figure 6 This is a SEM image of the liquid metal coating prepared in Example 2 of the present invention; Figure 6 It can be seen that the liquid metal composite powder can form a uniform coating on the surface of the substrate.

[0046] Figure 7 The liquid metal coating and its conductive performance diagram formed on the surface of one-dimensional, two-dimensional and three-dimensional materials in Examples 12-14 of the present invention; Figure 7 It can be seen that the rubbing coating method can be used to form a coating containing liquid metal powder on the surface of one-dimensional, two-dimensional and three-dimensional materials, and the obtained coating has good conductive properties.

[0047] Figure 8 The cycle curves of NCM||Cu and Li||Cu assembled by preparing the conductive coating in Example 16 of the present invention; Figure 8 It can be seen that the commercial copper foil coated with liquid metal has more stable cycling performance in the Li||Cu battery cycle than the commercial copper foil not coated with liquid metal, and achieves good first-cycle charge and discharge in the NCM||Cu battery.

[0048] Fig. 9 The liquid metal coating ( Fig. 9 c) Compared with the liquid metal powder in Example 1, the liquid metal powder was continuously subjected to a relatively large pressure (40N, Fig. 9 b) Continuous small pressure (0.2N, Fig. 9 a) Optical photograph of the uniformity of the conductive coating prepared by rubbing; Fig. 9 It can be seen that by optimizing the pressure during the wiping process, the uniformity of the conductive coating can be optimized. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0050] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0051] The present invention is based on a composite powder of liquid metal and functional filler. With the help of the good adhesion of the liquid metal surface oxide layer to the surface of other substances, a micro-nano coating of liquid metal and functional filler on the substrate surface is achieved through a rubbing coating method of repeated friction and extrusion, and finally a structurally stable, scratch-resistant composite coating with metal-level electrical and thermal conductivity properties is prepared, and the coating thickness can be controlled to be several nanometers to several microns.

[0052] The present invention provides a method for preparing a liquid metal coating, the method comprising:

[0053] The liquid metal composite is rubbed on the surface of the substrate to form a coating containing liquid metal; wherein the specific process of the rubbing includes: repeatedly rubbing the composite powder containing liquid metal on the surface of the substrate under pressure P1 and friction rate V1 to achieve uniform spreading of the composite powder containing liquid metal on the surface of the substrate; then continuing to rub repeatedly under pressure P2 and friction rate V2 until there is no excess powder and the rubbing is terminated to obtain a liquid metal coating.

[0054] The present invention brings the liquid metal composite into contact with the substrate surface by rubbing, and automatically realizes the forming of the liquid metal coating on any substrate surface under the action of the micro-adhesion force of the liquid metal and its surface oxide layer on the substrate surface, thereby preparing a liquid metal coating with submicron and nanometer thickness. The liquid metal coating is specifically a stable, scratch-resistant composite coating with metal-level conductive properties.

[0055] In the present invention, the thickness of the liquid metal coating is 1nm to 5μm; it can be seen that the present invention realizes the coating technology of the surface of liquid metal with submicron and nanometer thickness, further greatly reducing the thickness of the liquid metal coating. In some specific embodiments, the liquid metal composite loading in the liquid metal coating is 0.01 to 1 mg / cm 2 .

[0056] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0057] Example 1

[0058] A method for preparing a liquid metal coating comprises the following steps:

[0059] Step (a): mixing liquid metal (Ga 68.5%, In 21.5%, Sn 10% by mass) with artificial graphite in a mass ratio of 6:4, and then grinding in a mortar for 10 minutes for uniform dispersion to form a liquid metal composite powder that is easy to flow (particle size: ~50um, in the present invention, ~ represents approximately, and here means that the average particle size of the composite powder is about 50um);

[0060] Step (b): dispersing the liquid metal composite powder onto the surface of a foam of a certain size (1*1*1cm) to form a powder of a certain thickness (2mm);

[0061] Step (c): first, apply a pressure of 40N to the surface of the foam obtained in step (b), maintain the pressure and rub it repeatedly at a rate of 2cm / s until a uniform bright silver coating appears on the surface of the glass substrate (i.e., the composite powder containing liquid metal is evenly spread on the surface of the substrate); then adjust the pressure to 0.2N and rub it repeatedly at a rate of 10cm / s until a uniform coating is formed on the glass surface, and continue rubbing until there is no excess powder, and then stop rubbing to obtain a coating containing liquid metal, at which time the coating surface has a uniform gloss (such as Fig. 9 c).

[0062] If a small pressure (0.2N) is applied throughout the process, the liquid metal inside the liquid metal composite powder cannot be effectively spread on the substrate, and ultimately a uniform liquid metal coating cannot be formed (e.g. Fig. 9 a); If a large pressure (40N) is applied throughout the process, a large amount of liquid metal and a small amount of artificial graphite can spread on the substrate surface, but the final surface uniformity and smoothness are poor (such as Fig. 9 b).

[0063] The thickness of the coating containing liquid metal obtained in Example 1 is ˜600 nm; the surface color is black, and there is no obvious scratch after rubbing with 1000-grit sandpaper for 50 cm at a pressure of 0.5 kPa, indicating that it has scratch resistance and excellent mechanical stability.

[0064] Example 2

[0065] A method for preparing a liquid metal coating comprises the following steps:

[0066] Step (a): liquid metal (Ga 68.5%, In 21.5%, Sn 10%) and artificial graphite were mixed in a mass ratio of 5:5 and then ground in a mortar for 10 minutes for uniform dispersion to form a liquid metal composite powder (~15 μm) that is easy to flow;

[0067] Step (b): dispersing the liquid metal composite powder onto the surface of a foam of a certain size (1*1*1cm) to form a powder of a certain thickness (2mm);

[0068] Step (c): first, apply a pressure of 40 N to the foam, maintain the pressure, and rub it repeatedly at a rate of 2 cm / s until a uniform bright silver coating appears on the surface of the glass substrate; then adjust the pressure to 0.2 N and rub it repeatedly at a rate of 10 cm / s until a uniform coating is formed on the glass surface, and continue rubbing until there is no excess powder, thereby obtaining a liquid metal coating, and the coating surface has a uniform gloss.

[0069] The thickness of the coating containing liquid metal obtained in Example 2 is ˜1000 nm; the surface color is silver, and there is no obvious scratch after rubbing with 1000-grit sandpaper for 50 cm at a pressure of 0.5 kPa, indicating that it has scratch resistance and excellent mechanical stability.

[0070] Example 3

[0071] A method for preparing a liquid metal coating comprises the following steps:

[0072] Step (a): liquid metal (Ga 68.5%, In 21.5%, Sn 10%) and artificial graphite were mixed in a mass ratio of 8:2 and then ground in a mortar for 10 minutes for uniform dispersion to form a liquid metal composite powder (~15 μm) that is easy to flow;

[0073] Step (b): dispersing the liquid metal composite powder onto the surface of a foam of a certain size (1*1*1cm) to form a powder of a certain thickness (2mm);

[0074] Step (c): first, apply a pressure of 40 N to the foam, maintain the pressure, and rub it repeatedly at a rate of 2 cm / s until a uniform bright silver coating appears on the surface of the glass substrate; then adjust the pressure to 0.2 N and rub it repeatedly at a rate of 10 cm / s until a uniform coating is formed on the glass surface, and continue rubbing until there is no excess powder, thereby obtaining a liquid metal coating, and the coating surface has a uniform gloss.

[0075] The thickness of the coating containing liquid metal obtained in Example 3 is ~300nm; the surface color is silver, and obvious scratches appear after rubbing with 1000 mesh sandpaper for 50cm under a pressure of 0.5kPa. This is because the content of artificial graphite is too little and no protective graphite layer is formed, so the scratch performance of the obtained coating is poor.

[0076] Example 4

[0077] A method for preparing a liquid metal coating comprises the following steps:

[0078] Step (a): liquid metal (Ga 68.5%, In 21.5%, Sn 10%) and artificial graphite were mixed in a mass ratio of 3:7 and then ground in a mortar for 10 minutes for uniform dispersion to form a liquid metal composite powder (~15 μm) that is easy to flow;

[0079] Step (b): dispersing the liquid metal composite powder onto the surface of a foam of a certain size (1*1*1cm) to form a powder of a certain thickness (2mm);

[0080] Step (c): first, apply a pressure of 40 N to the foam, maintain the pressure, and rub it repeatedly at a rate of 2 cm / s until a uniform bright silver coating appears on the surface of the glass substrate; then adjust the pressure to 0.2 N and rub it repeatedly at a rate of 10 cm / s until a uniform coating is formed on the glass surface, and continue rubbing until there is no excess powder, thereby obtaining a liquid metal coating, and the coating surface has a uniform gloss.

[0081] The thickness of the coating containing liquid metal obtained in Example 4 is 2 μm; no obvious scratches were found after rubbing with 1000-grit sandpaper for 50 cm at a pressure of 0.5 kPa, indicating that it has scratch resistance and excellent mechanical stability. Table 1 summarizes and compares the properties of the coating containing liquid metal obtained by rubbing in Examples 1-4.

[0082] Table 1 Properties of the liquid metal coatings obtained by rubbing method in Examples 1-4

[0083] serial number Whether a coating is formed Coating thickness Mechanical stability of coating (sandpaper abrasion test) Example 1 yes ~600nm No scratches Example 2 yes ~1um No scratches Example 3 yes ~300nm Scratches Example 4 yes ~2um No scratches

[0084] Example 5

[0085] A method for preparing a liquid metal coating comprises the following steps:

[0086] Step (a): mixing liquid metal (Ga 68.5%, In 21.5%, Sn 10%) and artificial graphite in a mass ratio of 5:5, and then grinding in a mortar for 10 minutes to uniformly disperse the mixture to form a liquid metal composite powder that is easy to flow;

[0087] Step (b): dispersing the liquid metal composite powder onto the surface of a foam of a certain size (1*1*1cm) to form a powder of a certain thickness (2mm);

[0088] Step (c): first, apply a pressure of 40N to the foam, maintain the pressure and rub it repeatedly at a rate of 2cm / s until a uniform bright silver coating appears on the surface of the copper foil substrate; then adjust the pressure to 0.2N and rub it repeatedly at a rate of 10cm / s until a uniform black coating is formed on the surface of the copper foil, and continue rubbing until there is no excess powder, thereby obtaining a liquid metal coating, and the coating surface has a uniform gloss.

[0089] The thickness of the liquid metal coating obtained in Example 5 is 800 nm; and there is no obvious scratch after rubbing with 1000-grit sandpaper for 50 cm under a pressure of 0.5 kPa, which shows scratch resistance and excellent mechanical stability.

[0090] Example 6

[0091] A method for preparing a liquid metal coating comprises the following steps:

[0092] Step (a): mixing liquid metal (Ga 68.5%, In 21.5%, Sn 10%) and artificial graphite in a mass ratio of 5:5, and then grinding in a mortar for 10 minutes to uniformly disperse the mixture to form a liquid metal composite powder that is easy to flow;

[0093] Step (b): Disperse the liquid metal composite powder onto the surface of a foam of a certain size (1*1*1 cm) to form a powder of a certain thickness (2 mm).

[0094] Step (c): first apply a pressure of 30N to the foam, maintain the pressure and rub it repeatedly at a rate of 1.5cm / s until a uniform bright silver coating appears on the surface of the 3D ceramic substrate; then adjust the pressure to 0.3N and rub it repeatedly at a rate of 6cm / s until a uniform black coating is formed on the surface of the 3D ceramic substrate, and continue rubbing until there is no excess powder, thereby obtaining a liquid metal coating, and the coating surface has a uniform gloss.

[0095] The thickness of the coating containing liquid metal obtained in Example 6 is ~1 um.

[0096] Example 7

[0097] A method for preparing a liquid metal coating comprises the following steps:

[0098] Step (a): Mix liquid metal (GaIn alloy: mass ratio Ga 80:In 20) and LiCoO2 in a mass ratio of 5:5 and grind them in a mortar for 10 minutes to uniformly disperse them to form a liquid metal composite powder (~15 μm) that is easy to flow;

[0099] Step (b): dispersing the liquid metal composite powder onto the surface of a foam of a certain size (1*1*1cm) to form a powder of a certain thickness (2mm);

[0100] Step (c): first, apply a pressure of 40 N to the foam, maintain the pressure, and rub it repeatedly at a rate of 2 cm / s until a uniform bright silver coating appears on the surface of the glass substrate; then adjust the pressure to 0.2 N and rub it repeatedly at a rate of 10 cm / s until a uniform coating is formed on the glass surface, and continue rubbing until there is no excess powder, thereby obtaining a liquid metal coating, and the coating surface has a uniform gloss.

[0101] The thickness of the coating containing liquid metal obtained in Example 2 is 800 nm; there is no obvious scratch after rubbing with 1000-grit sandpaper for 50 cm under a pressure of 0.5 kPa, indicating that it has scratch resistance and excellent mechanical stability.

[0102] Embodiment 8-11

[0103] In Examples 8-11, based on Example 1, only the types of liquid metal and solid filler are adjusted, and the remaining steps and parameters are the same; the specific types of liquid metal and solid filler and the resulting coating thickness in each example are shown in Table 2.

[0104] Table 2 Types of liquid metals and solid fillers used in Examples 8-11

[0105] serial number Liquid Metal Solid filler Coating thickness Example 8 Ga metal Artificial graphite ~300nm Example 9 GaInSn alloy <![CDATA[LiFeO4]]> ~500nm Example 10 Mercury Metal Copper powder ~400nm Embodiment 11 Lithium Metal Zinc powder ~800nm

[0106] Example 12

[0107] A method for preparing a liquid metal coating comprises the following steps:

[0108] Step (a): 20uL of liquid metal (Ga 68.5%, In 21.5%, Sn 10%) is dropped onto the foam surface to form a coating area enriched with liquid metal;

[0109] Step (b): placing the optical fiber in the liquid metal droplet-enriched portion, applying pressure to the foam while pulling the optical fiber (pressure: 5N; pulling rate: 5cm / s);

[0110] Step (c): Liquid metal is uniformly coated on the surface of the optical fiber by means of pressure, friction and repeated pulling of the optical fiber to obtain a liquid metal coating.

[0111] The thickness of the liquid metal coating obtained in Example 12 is ∼220 nm.

[0112] Embodiment 13

[0113] A method for preparing a liquid metal coating comprises the following steps:

[0114] Step (a): drop 20uL of liquid metal (Ga 68.5%, In 21.5%, Sn 10%) onto the paper surface;

[0115] Step (b): first, apply a pressure of 30 N to the foam, maintain the pressure and rub it repeatedly at a rate of 1.5 cm / s until a uniform bright silver coating appears on the surface of the paper; then adjust the pressure to 0.3 N and rub it repeatedly at a rate of 6 cm / s until there is no obvious particle aggregation on the surface of the bright silver coating on the paper, thereby obtaining a liquid metal coating, and the coating surface has a uniform gloss.

[0116] The thickness of the resulting liquid metal coating was ~100 nm.

[0117] Embodiment 14

[0118] A method for preparing a conductive foam material (composite conductive material) containing a liquid metal coating, specifically comprising the following steps:

[0119] Step (a): drop 100uL of liquid metal (Ga 68.5%, In 21.5%, Sn 10%) onto the surface of the copper foil;

[0120] Step (b): applying a pressure of 30N to the foam, repeatedly rubbing the liquid metal on the copper foil substrate, controlling the rubbing area to be constant, until the foam on the side contacting the liquid metal turns silver;

[0121] Step (c): Perform the operation of step (b) on the other sides of the foam until all sides become silver; finally, the conductive foam is obtained.

[0122] Embodiment 15

[0123] A method for preparing a liquid metal coating comprises the following steps:

[0124] Step (a): drop 20uL of liquid metal (Ga 68.5%, In 21.5%, Sn 10%) onto the glass surface;

[0125] Step (b): first, apply a pressure of 30 N to the foam, maintain the pressure and rub it repeatedly at a rate of 1.5 cm / s until a uniform bright silver coating appears on the glass surface; then adjust the pressure to 0.3 N and rub it repeatedly at a rate of 6 cm / s until there are no obvious particle aggregates on the surface of the bright silver coating on the glass surface, thereby obtaining a liquid metal coating, and the coating surface has a uniform gloss.

[0126] The thickness of the resulting liquid metal coating was ~100 nm.

[0127] Example 16

[0128] A method for applying a liquid metal coating to an anode-free lithium metal battery, the specific process comprising:

[0129] Step (a): drop 20uL of liquid metal (Ga 68.5%, In 21.5%, Sn 10%) onto the surface of the copper foil;

[0130] Step (b): First, apply 30N pressure to the foam, maintain the pressure and rub it repeatedly at a rate of 1.5cm / s until a uniform bright silver coating appears on the copper foil surface; then adjust the pressure to 0.3N and rub it repeatedly at a rate of 6cm / s until there is no obvious particle aggregation on the bright silver coating surface of the copper foil to obtain a liquid metal coating, at which time the coating surface has a uniform gloss. The coating thickness range of the copper foil surface is ~50nm;

[0131] Step (c): Use a cutter to cut the coated copper foil into discs with a diameter of 18 mm as the negative electrode of the battery; NCM811 (loading 9 mg / cm -2 ) as the positive electrode; Celargd 2400 as the separator; 1MLiTFSI (DOL / DME) + 2% LiNO3 as the electrolyte to assemble the button cell;

[0132] Step (d): using a cutter to cut the coated copper foil into discs with a diameter of 18 mm as the positive electrode of the battery; lithium metal as the negative electrode; Celargd 2400 as the separator; 1MLiTFSI (DOL / DME) + 2% LiNO3 as the electrolyte to assemble a button cell;

[0133] Step (e): After the batteries prepared in step c and step d were left to stand for 10 h, the electrochemical cycling performance of NCM||Cu (current density of 0.05C) and Li||Cu battery (current density of 0.5 mA cm) were tested using the Xinwei test system. -2 , with a surface capacity of 0.5 mAh cm -2) at 25°C. The commercial electrolytic copper foil coated with liquid metal has more stable cycling performance in Li||Cu battery cycles than the commercial electrolytic copper foil without liquid metal coating (Guangdong Jiayuan Technology Co., Ltd.), and achieves good first cycle charge and discharge in NCM||Cu battery (such as Figure 8 shown).

[0134] Comparative Example 1

[0135] The method of preparing liquid metal coating by adhesion transfer method, the experimental process is as follows:

[0136] A glass rod was used to scrape 50uL of liquid metal (commercial; GaInSn liquid metal; Dongguan Dingguan Metal Technology Co., Ltd.) onto the surface of a glass substrate (2.5*6*0.5cm) until the surface was uniform and smooth, and then a glass substrate of the same area was used to cover the surface of the liquid metal coating, and a pressure of 30N was used to press the liquid metal to make close contact with the second glass substrate. Subsequently, the second glass plate was peeled off in a direction perpendicular to the liquid metal surface to obtain a liquid metal coating prepared by the adhesion transfer method.

[0137] Comparative Example 2

[0138] The method of preparing liquid metal coating by scraping method, the experimental process is as follows:

[0139] 50 uL of liquid metal (commercial; GaInSn liquid metal; Dongguan Dingguan Metal Technology Co., Ltd.) was scraped onto the surface of a glass substrate (2.5*6*0.5 cm) using a glass rod until the surface was uniform and smooth, thereby obtaining a liquid metal coating prepared by scraping.

[0140] Comparative Example 3

[0141] Liquid metal composite powder is processed by adhesion transfer method to prepare liquid metal coating. Experimental process:

[0142] 0.5 g of liquid metal composite powder (prepared in Example 2) was scraped (0.5 cm / s) onto the surface of a glass substrate (2.5*6*0.5 cm) using a glass rod, and then a glass substrate of the same area was used to cover the surface of the liquid metal composite, and a pressure of 30 N was used to press the liquid metal composite to make it in close contact with the second glass substrate. Subsequently, the second glass plate was peeled off in a direction perpendicular to the surface of the liquid metal composite. Since the adhesive transfer method mainly applies pressure to the composite powder, there is no obvious friction; therefore, the processing of the liquid metal composite powder cannot be achieved using this method.

[0143] Comparative Example 4

[0144] Liquid metal composite powder is processed by scraping method to prepare liquid metal coating. Experimental process:

[0145] 0.5 g of the liquid metal composite (prepared by step (a) in Example 2) was scraped (0.5 cm / s) onto the surface of a glass substrate (2.5*6*0.5 cm) using a glass rod. Since the scraping method has a small friction force, the liquid metal inside the liquid metal composite cannot be released. Therefore, this method cannot be used to process liquid metal composite powder.

[0146] Comparative Example 5

[0147] A method for preparing a liquid metal coating comprises the following steps:

[0148] Step (a): liquid metal (Ga 68.5%, In 21.5%, Sn 10%) and artificial graphite were mixed in a mass ratio of 2:8 and then ground in a mortar for 10 minutes for uniform dispersion to form a liquid metal composite powder (~15 μm) that is easy to flow;

[0149] Step (b): dispersing the liquid metal composite powder onto the surface of a foam of a certain size (1*1*1cm) to form a powder of a certain thickness (2mm);

[0150] Step (c): first, apply a pressure of 40 N to the foam, maintain the pressure, and rub it repeatedly at a rate of 2 cm / s until a uniform bright silver coating appears on the surface of the glass substrate; then adjust the pressure to 0.2 N and rub it repeatedly at a rate of 10 cm / s until a uniform coating is formed on the glass surface, and continue rubbing until there is no excess powder, thereby obtaining a liquid metal coating, and the coating surface has a uniform gloss.

[0151] In Comparative Example 5, no coating containing liquid metal was obtained, and the glass surface showed agglomerates of some black particles.

[0152] Test method:

[0153] Surface uniformity test: Observe the coating surface status through digital photos and microscope photos.

[0154] Abrasion resistance test: Place one side of the glass plate with liquid metal coating downward, facing 1000 grit sandpaper, then apply a 70N weight to the back of the glass substrate, push the glass plate on the sandpaper to move 50cm, and observe the scratches on the liquid metal surface.

[0155] Peeling performance test: Use 3M tape to stick on the surface of the liquid metal coating, use a certain pressure (5N) to ensure stable contact between the tape and the liquid metal, then apply tension to the tape in a direction perpendicular to the surface of the liquid coating, peel off the tape at a rate of 0.005m / s, and observe the remaining coating on the liquid metal surface.

[0156] result:

[0157] It can be seen from the optical photographs of Example 15 and Comparative Examples 1 and 2 that ( Figure 4 ):

[0158] The surface of the liquid metal coating prepared by the adhesion transfer method and the scraping method has uneven liquid metal droplets; while the surface of the liquid metal coating prepared by the wiping method is more uniform (Example 10).

[0159] It can be seen from the optical photographs of Example 2 and Comparative Examples 3 and 4 that ( Figure 4 ):

[0160] The adhesion transfer method and the scraping method cannot realize the processing of liquid metal composite powder. This is because the adhesion transfer method mainly applies pressure to the composite powder without obvious friction; the scraping method cannot realize the release of liquid metal inside the liquid metal composite because of the small friction; the uniform coating of the liquid metal composite is achieved by the rubbing method.

[0161] From the test results of Example 2 and Comparative Examples 1 and 2, it can be seen that ( Figure 5 ):

[0162] 1) From the optical and microscopic photos after the coating is prepared, it can be seen that the surface of the liquid metal obtained by the adhesion transfer method is the roughest, and the surface of the composite conductive coating prepared by the rubbing method of the present invention is the smoothest; 2) In the optical photos of the wear experiment (the coating moves 50cm on 1000-mesh sandpaper under a pressure of 0.5kPa), the coatings obtained by the adhesion transfer method and the scraping method have obvious scratches, while the surface of the composite conductive coating prepared by the scraping method has no obvious scratches. In addition, the microscopic photos also confirm the above results. 3) The composite conductive coating prepared by the scraping method also shows good peeling resistance in the tape peeling test (3M test tape peeled 3 times), and the performance is better than the coatings prepared by the adhesion transfer method and the scraping method. Comparison shows that the scraping method used in the present invention has the following advantages: 1. It realizes the uniform processing of the liquid metal composite and improves the mechanical stability of the coating; 2. It further reduces the thickness of the liquid metal coating, improves the uniformity of the coating surface, and expands the scene application range of the coating (1D-3D structure processing).

[0163] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A coating containing liquid metal, characterized in that: The coating is a uniform coating containing liquid metal formed by coating a composite powder containing liquid metal on the surface of a substrate; wherein the composite powder containing liquid metal is a mixture of liquid metal and solid filler, the weight ratio of the liquid metal to the solid filler is: 30 to 90 parts by weight of liquid metal, 10 to 70 parts by weight of solid filler, and the total weight of the liquid metal and the solid filler is 100 parts; The liquid metal includes: at least one of gallium metal, gallium-indium alloy, gallium-indium-tin alloy, mercury metal, francium metal, cesium metal, lithium metal, sodium metal, potassium metal, rubidium metal, cadmium metal or bismuth metal; the solid filler includes: carbon-based solid filler, metal oxide, solid metal filler, solid ceramic filler or electrode active particle filler; wherein, the carbon-based solid filler includes: at least one of natural graphite, artificial graphite, graphene powder, carbon nanotube powder or carbon micro-nanosphere powder; the solid ceramic filler includes: boron carbide, chromium carbide, molybdenum carbide, silicon carbide, titanium carbide, zirconium carbide, vanadium carbide, aluminum nitride, boron nitride, silicon nitride, titanium nitride, chromium diboride, titanium diboride, zirconium diboride, ZIF material, MoS2, Li 6.5 LqCy 1.5 Ta 0.5 O 12 、Li7La3Zr2O 12 、LiTi2(PO4)3、LiGe2(PO4) 3、 Li6PS5Cl, Li6PS5 Br, Li6PS5 I, Li 10 GeP2S 12 and Li7P3S 11 The metal oxides include at least one of indium oxide, gallium oxide, tin oxide, ferroferric oxide, ferrous oxide, manganese oxide, chromium oxide, aluminum oxide, titanium dioxide, silicon dioxide, nickel oxide, calcium oxide, magnesium oxide, barium oxide, copper oxide or molybdenum oxide; the solid metal filler includes at least one of silver powder, gold powder, copper powder, aluminum powder, zinc powder, magnesium powder, tin powder, iron powder, tungsten powder, molybdenum powder, nickel powder, cobalt powder, lead powder, titanium powder or tantalum powder; the electrode active particle filler includes LiCoO2, NCM, LiMn2O4, LiFeO4 and LiNi 0.8 Co 0.15 Al 0.05 At least one of O2; In addition, the coating containing liquid metal is prepared by the following method: a composite powder containing liquid metal is used to form a uniform coating containing liquid metal on the surface of a substrate by a rubbing process, and the rubbing process is as follows: the composite powder containing liquid metal is brought into contact with the surface of the substrate, and firstly, the liquid metal in the powder is spread evenly on the surface of the substrate by repeated rubbing at a pressure P1 and a friction rate V1; then, the surface of the substrate is made to show a uniform bright color and no excess powder by repeated rubbing at a pressure P2 and a friction rate V2; that is, a uniform coating containing liquid metal is formed; P1=1N~300N, P2=0.1N~35N, V1=1~10 cm / s, V2=1~30 cm / s.

2. A coating containing liquid metal according to claim 1, characterized in that: The weight ratio of the liquid metal to the solid filler is: 30 to 70 parts by weight of the liquid metal and 30 to 70 parts by weight of the solid filler.

3. The coating containing liquid metal according to claim 1, characterized in that: The thickness of the coating containing liquid metal is 1 nm to 5 μm.

4. The coating containing liquid metal according to claim 1, characterized in that: The coating containing liquid metal had no obvious scratches after being rubbed with 1000-grit sandpaper for 50 cm under a pressure of 0.5 kPa.

5. A coating containing liquid metal according to claim 1 or 2, characterized in that: The particle size of the composite powder containing liquid metal is 1-100 μm.

6. A coating containing liquid metal according to any one of claims 1 to 3, characterized in that: The P1=3N~80N, P2=0.5N~30N.

7. A coating containing liquid metal according to any one of claims 1 to 4, characterized in that: The substrate is: one-dimensional fiber, two-dimensional film or sheet, porous material with three-dimensional structure, or irregular block.

8. A coating containing liquid metal according to claim 7, characterized in that: The one-dimensional fiber includes: polymer fiber, glass fiber or basalt fiber; the two-dimensional film or sheet includes: polymer film or metal foil; the porous material with three-dimensional structure includes: foam, ceramic product or inner wall of pipe.

9. The method for preparing a coating containing liquid metal according to any one of claims 1 to 8, characterized in that: The preparation method comprises: forming a uniform coating containing liquid metal on the surface of a substrate by a rubbing method using a composite powder containing liquid metal, and the rubbing method comprises: contacting the composite powder containing liquid metal with the surface of a substrate, firstly rubbing repeatedly at a pressure P1 and a friction rate V1 so that the liquid metal in the powder can be evenly spread on the surface of the substrate; then rubbing repeatedly at a pressure P2 and a friction rate V2 so that the surface of the substrate shows a uniform bright color and has no excess powder, that is, forming a uniform coating containing liquid metal; P1=1N~300N, P2=0.1N~35N, V1=1~10 cm / s, V2=1~30 cm / s.

10. The method for preparing a coating containing liquid metal according to claim 9, characterized in that: The P1=3N~80N, P2=0.5N~30N.

11. The method for preparing a coating containing liquid metal according to claim 9, characterized in that: In the method, a flexible and easily deformable tool material is used for wiping, and the tool material includes: porous plastic foam, fiber felt, rubber sheet or cellulose-based film.

12. The method for preparing a coating containing liquid metal according to claim 11, characterized in that: The preparation method comprises the following steps: 1). Prepare a mixture of liquid metal and solid filler to form a composite powder that is easy to flow; 2). Dispersing the composite powder onto the surface of a substrate to be coated, or onto the surface of a flexible wiping tool material; 3). Apply pressure and friction to the composite powder and the substrate to be coated by a flexible wiping tool material. First, the composite powder is evenly spread on the substrate surface by repeated wiping at a pressure of P1 and a friction rate of V1; then, the substrate surface coating is uniform and free of excess powder by repeated wiping at a pressure of P2 and a friction rate of V2; then, the excess powder is removed to form a uniform, stable and strong coating containing liquid metal; the liquid metal automatically forms a composite coating on any surface under the micro-adhesion force of its surface oxide, solid filler and substrate.

13. Application of a coating containing liquid metal in 1D, 2D, 3D conductive materials or anode-free lithium metal batteries, wherein the coating containing liquid metal is a coating as described in any one of claims 1 to 8, or a coating prepared by the method as described in any one of claims 9 to 12.

Citation Information

Patent Citations

  • Zinc ion battery liquid metal composite negative electrode and preparation method and application thereof

    CN111916744A

  • Modified liquid metal composite material capable of being directly formed and preparation method thereof

    CN113717701A